Demystifying Zero Trust Architecture: Why It's Not Just a Buzzword - Narra, Sujatha Lakshmi (International Journal of Computing and Engineering, 2025)
This article examines Zero Trust Architecture (ZTA) as a fundamental shift in cybersecurity philosophy rather than merely an industry buzzword. Drawing from multiple empirical studies and implementation frameworks, It explores how traditional perimeter-based security models have proven inadequate against modern threat vectors, particularly in environments with cloud adoption and remote work. The article details the core technical components of Zero Trust, including robust identity and access management, microsegmentation, continuous monitoring, and centralized policy enforcement. Through analysis of financial sector implementations, It documents the transformative impact of Zero Trust across organizational security postures. It demonstrates that ZTA provides measurable benefits in breach containment, attack surface reduction, and security operations efficiency while addressing significant implementation challenges such as legacy system integration and performance optimization. Using a phased implementation approach, organizations can systematically transition from traditional security models to a comprehensive Zero Trust framework that aligns with modern business requirements while providing substantially improved protection against evolving threats.